2016
DOI: 10.1088/1475-7516/2016/02/045
|View full text |Cite
|
Sign up to set email alerts
|

From wires to cosmology

Abstract: We provide a statistical framework for characterizing stochastic particle production in the early universe via a precise correspondence to current conduction in wires with impurities. Our approach is particularly useful when the microphysics is uncertain and the dynamics are complex, but only coarse-grained information is of interest. We study scenarios with multiple interacting fields and derive the evolution of the particle occupation numbers from a Fokker-Planck equation. At late times, the typical occupati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(127 citation statements)
references
References 75 publications
7
119
1
Order By: Relevance
“…In particular, we exploit an analogy between the localization of electron energy eigenstates along a one-dimensional wire in the presence of disorder, and the localization of mass eigenstates along a local theory space with random mass parameters on each site. (Similar analogies have been made for inflation [20,21] and gravity [22].) All mass eigenstates are exponentially localized, and can thus have exponentially suppressed couplings to sites in the theory space-the lightest (and heaviest) eigenstates especially so.…”
mentioning
confidence: 59%
“…In particular, we exploit an analogy between the localization of electron energy eigenstates along a one-dimensional wire in the presence of disorder, and the localization of mass eigenstates along a local theory space with random mass parameters on each site. (Similar analogies have been made for inflation [20,21] and gravity [22].) All mass eigenstates are exponentially localized, and can thus have exponentially suppressed couplings to sites in the theory space-the lightest (and heaviest) eigenstates especially so.…”
mentioning
confidence: 59%
“…In particular, self-resonance, where the homogeneous inflaton condensate pumps energy into its own fluctuations, can lead to interesting nonlinear effects even in absence of couplings to other fields (e.g., [23][24][25]). Such explosive particle production, formation of nontopological and topological solitons (e.g., [23,26]), as well as relics such as black holes (e.g., [27]) and primordial gravitational waves (e.g., [28][29][30]), amongst others, make 1 See [12][13][14] for attempts at some model-independent approaches. reheating an exciting dynamical playground.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that changing δ to 0.100 describes well the time the equation of state approaches w rad ¼ 1=3, as shown on the bottom. 12 For the calculation of the inflaton potential parameters in Sec. IV, we have used the value of A s measured at k ⋆ ¼ 0.05 Mpc −1 .…”
mentioning
confidence: 99%
“…It can therefore be shown that the problem of finding the Bogoliubov coefficients which relate these two sets of asymptotic solutions for ϕ k (t) is mathematically equivalent to the problem of determining the transmission coefficients for scattering off a potential V (x) ∝ −sech 2 (x) in non-relativistic quantum mechanics [54]. Thus, by analogy, we find that the differential energy density dρ (p) λ0 /dk of inflaton field quanta per unit comoving momentum k at the time the non-adiabatic evolution effectively ceases -which is roughly equivalent to the time at which φ λ0 is released from the slingshot -takes the form dρ (p) λ0 dk ≈ 4πk 2 cos 2 π 2 1 + λ 2 0 (t p )∆ 2 G (2π) 3 sinh 2 π 2 ∆ G k .…”
Section: Conclusion and Discussionmentioning
confidence: 99%